Myanmar : Beyond Politics to Societal Imperatives - Than, Tin Maung Maung; Taylor, Robert H.; Kyaw, Yin Hlaing (Book collections on Project MUSE., 2005)
Seeking to look beyond the day-to-day headlines and judgemental comments on developments in Myanmar, this volume gets under the surface to look at the underlying issues which the country faces regardless of its political future. After looking back to essay the historical forces and human agencies which have shaped contemporary Myanmar, the volume addresses health care and public policy provision with suggestions as to what potential roles the international community might have in assisting Myanmar's future socioeconomic development. Myanmar: Beyond Politics to Societal Imperatives broadens the debate on this state of more than 50 million people beyond the usual narrow didactics about democratization and economic policies.